Pelestarian Nilai-Nilai Sumang Pada Kearifan Lokal Didong Sebagai Perwujudan Masyarakat Yang Berkarakter - Saputra, Edy; Zulmaulida, Rahmy (Jumper: Journal of Educational Multidisciplinary Research, 2023)
Local wisdom in Gayo society has been passed down from generation to generation, two of which are Sumang and Didong. Sumang is a cultural system that has roots in the Gayo people as an archetype and foundation of life. Meanwhile, Didong is a local art from the Gayo area that combines vocal, dance and literature. This research uses a type of qualitative research with a descriptive approach, which aims to preserve and restore the implementation of Sumang and Didong, as well as to describe the acceptance of the Gayo Highlands community towards the idea of ​​implementing Sumang values ​​into Didong art in order to achieve a society with character. All formal and non-formal art galleries and the Ceh Didong in the Gayo Highlands became the population in this study, with the sample being the Renggali Studio and 3 Cehs. Data collection techniques using observation and interviews. Research data were analyzed using descriptive data analysis techniques from observations and interviews. The results of the study show that: (1) the people of Gayo Highlands agree with the idea of ​​applying Sumang values ​​to Didong art, and (2) the role of the younger generation through actual practice of applying Sumang values ​​in their activities and exemplifying the application of Sumang values ​​to in Didong art without changing the characteristics of Didong art.